ANALYSIS OF PHYSICAL AND CHEMICAL PROPERTIES OF HYDROCARBON WASTE (World Bulletin of Social Sciences, 2021)
The article presents the results of determining the physicochemical properties of diluted oil sludge with various diluents. The optimal operating parameters of the bitumen production process have been determined: softening temperature according to a softening point (“ method of ring and ball” ); depth of needle penetration. The correspondence of the obtained bitumen to the standards has been determined. The fractional composition of the diluted oil sludge was determined.